Sistem Pendukung Keputusan Penerimaan Beasiswa Menggunakan Metode Weighted Product - Anisa, Desfa; Ningrum, Widya Septya; Kusumo, Retno; Putri, Widya (TIN: Terapan Informatika Nusantara, 2022)
This decision support system was created to assist the school in making decisions related to the problem of selecting scholarships for students who really deserve to get scholarships, where the process of selecting scholarships for underprivileged students is still done manually. From each prospective scholarship recipient will be selected based on criteria, these criteria consist of parents' occupations, parents' income, number of dependents of parents and the average value of report cards. The method used in the scholarship selection process is the WP method. The WP method or the Weighted Product method is one of the methods used in helping the decision-making process by multiplying, where each attribute rating will be raised to the power of each weight. After that, the final result of the calculation of the Weighted Product method will be a ranking process that will determine the chosen alternative in the process of determining scholarship acceptance. The purpose of this research is to assist the school in the process of selecting scholarships for underprivileged students. The design of this decision support system uses Unified Modeling Language diagrams and is built using the PHP programming language and MySQL database. The results of the calculations that have been carried out using the Weighted Product method, the results with the highest value are found in alternative A8 with a value of 0.2012 so that alternative A8 is the best alternative and can be used as a recommendation for prospective scholarship recipients